2019
DOI: 10.1101/620708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Palmitoylation controls the stability of 190 kDa Ankyrin-G in dendritic spines and is regulated by ZDHHC8 and lithium

Abstract: The ANK3 gene, which encodes ankyrin-G (AnkG), is associated with a variety of neuropsychiatric and cognitive disorders including bipolar disorder, autism spectrum disorder, and schizophrenia. These diseases are characterized by abnormal dendritic and synaptic architecture. AnkG is a multifunctional scaffold protein with several isoforms: The 480 kDa and 270 kDa isoforms have roles at the axon initial segment and node of Ranvier, but the function of the 190 kDa isoform (AnkG-190) is less well understood. Moreo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In unpolarized MDCK cells, a C70A mutation abolishes the association of Ankyrin-G-190 with lateral membrane, suggesting palmitoylation at Cys70 is required for cellular localization of Ankyrin-G-190 [ 106 ]. Of particular interest, a very recent study carried out in cultured rat primary cortical neurons showed that palmitoylation at Cys70 stabilizes Ankyrin-G-190 in spine heads and at dendritic plasma membrane nanodomains to maintain the dendrite and spine architecture (Preprint [ 290 ]). Mutated ankyrin-G-190 C70A displayed a diffuse distribution with decreased nanodomains in spine and dendrites (Preprint [ 290 ]).…”
Section: Palmitoylation Of Ampar and Its Associated Scaffold Proteinsmentioning
confidence: 99%
See 4 more Smart Citations
“…In unpolarized MDCK cells, a C70A mutation abolishes the association of Ankyrin-G-190 with lateral membrane, suggesting palmitoylation at Cys70 is required for cellular localization of Ankyrin-G-190 [ 106 ]. Of particular interest, a very recent study carried out in cultured rat primary cortical neurons showed that palmitoylation at Cys70 stabilizes Ankyrin-G-190 in spine heads and at dendritic plasma membrane nanodomains to maintain the dendrite and spine architecture (Preprint [ 290 ]). Mutated ankyrin-G-190 C70A displayed a diffuse distribution with decreased nanodomains in spine and dendrites (Preprint [ 290 ]).…”
Section: Palmitoylation Of Ampar and Its Associated Scaffold Proteinsmentioning
confidence: 99%
“…Of particular interest, a very recent study carried out in cultured rat primary cortical neurons showed that palmitoylation at Cys70 stabilizes Ankyrin-G-190 in spine heads and at dendritic plasma membrane nanodomains to maintain the dendrite and spine architecture (Preprint [ 290 ]). Mutated ankyrin-G-190 C70A displayed a diffuse distribution with decreased nanodomains in spine and dendrites (Preprint [ 290 ]). Differing from the Ankyrin-G-190 palmitoylation in MDCK and HEK293 cells [ 107 ], only ZDHHC8, but not ZDHHC5, catalyzes the palmitoylation of Ankyrin-G-190 in dendritic spines (Preprint [ 290 ]).…”
Section: Palmitoylation Of Ampar and Its Associated Scaffold Proteinsmentioning
confidence: 99%
See 3 more Smart Citations